2021
DOI: 10.1039/d1ee01395e
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering the alternating synergy between interlayer Pt single-atom and NiFe layered double hydroxide for overall water splitting

Abstract: Single-atom catalysts (SACs) have enormous significance for heterogeneous catalysis. However, understanding how SACs function at molecular level remains as a huge challenge. Here, we report a general approach to anchor...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
142
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 231 publications
(161 citation statements)
references
References 58 publications
1
142
0
Order By: Relevance
“…It is worth mentioning that one of the first reports, in 1983, on the electrocatalytic performance of metal hydroxides, revealed a good OER activity of α-Ni(OH) 2 [57], and it was further confirmed that the Fe impurities in the α-Ni(OH) 2 greatly lower the OER overpotential [58,59]. Since then, the LDHs of 3d iron group metals (Fe, Co and Ni)-such as Ni-Fe [60][61][62][63][64], Ni-Co [65][66][67][68], Co-Ni [69][70][71], Fe-Ni [72][73][74], Fe-Co [75][76][77][78], and Co-Co [79][80][81][82]-and the corresponding derivatives-e.g., NiFe 2 O 4 [83][84][85][86], CoFe 2 O 4 [87], NiCo 2 O 4 [88,89], and Co 3 O 4 [90][91][92]-have been employed as OER or bifunctional ORR/OER electrocatalysts with high kinetics in alkaline solution.…”
Section: Introductionmentioning
confidence: 94%
“…It is worth mentioning that one of the first reports, in 1983, on the electrocatalytic performance of metal hydroxides, revealed a good OER activity of α-Ni(OH) 2 [57], and it was further confirmed that the Fe impurities in the α-Ni(OH) 2 greatly lower the OER overpotential [58,59]. Since then, the LDHs of 3d iron group metals (Fe, Co and Ni)-such as Ni-Fe [60][61][62][63][64], Ni-Co [65][66][67][68], Co-Ni [69][70][71], Fe-Ni [72][73][74], Fe-Co [75][76][77][78], and Co-Co [79][80][81][82]-and the corresponding derivatives-e.g., NiFe 2 O 4 [83][84][85][86], CoFe 2 O 4 [87], NiCo 2 O 4 [88,89], and Co 3 O 4 [90][91][92]-have been employed as OER or bifunctional ORR/OER electrocatalysts with high kinetics in alkaline solution.…”
Section: Introductionmentioning
confidence: 94%
“…Except for LDHs with Ru single atoms, Pt single atoms into Ni 3 Fe LDH (Ni 3 Fe LDH‐Pt SA) was prepared via a two‐step strategy with anion exchange and space‐confined electroreduction [19] . Ni 3 Fe LDH‐Pt SA catalyst brought outstanding HER performance with overpotential of 45 mV at 10 mA cm −2 and Tafel slope of 37.8 mV dec −1 , which is better than commercial 20 wt% Pt/C with 51 mV and 41.7 mV dec −1 , respectively.…”
Section: Ldh‐based Materials As Her Electrocatalystmentioning
confidence: 99%
“…Thereinto, CPE 1 and R 1 (represent electron transferability), CPE 2 and R 2 (represent Volmer step), CPE 3 and R 3 (represent Heyrovsky step) are presented in HER conditions. [29] Wherein, given the low-frequency relaxation decreased rapidly and shifted to higher frequencies at higher potential, CPE 2 and R 2 can be omitted at high potential, and the equivalent circuit model can be simplified accordingly (Figure S30 and S31).…”
Section: Forschungsartikelmentioning
confidence: 99%